Code-Switching and Code Mixing in Najwa Note Podcast with Maudy Ayunda - Modesta Hemal; Ni Made Diana Erfiani; Yohanes Octovianus L. Awololon (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2023)
In recent years, podcast content on YouTube and social media has been in great demand by the wider community. Especially one of the podcasts from Najwa Shihab's YouTube channel, which is the object of this research. The selection of the object is based on the story used by Najwa Shihab and the guest star in the podcast, Maudy Ayunda. Throughout the video, they use Indonesian as well as English. In addition, both also inserted elements of English words. This study aimed to describe types of code-switching and code-mixing in the Najwa Shihab podcast with Maudy Ayunda. This research is descriptive-qualitative research. The results of the analysis of this study revealled that there are types of code switching with Indonesian to English speech and vice versa, namely English to Indonesian. In addition, there was an insertion of English elements in the speech between the presenter and the speaker.